Implementation and evaluation of a Project ECHO telementoring program for the Namibian HIV workforce - Leonard Bikinesi; Gillian O’Bryan; Clay Roscoe; Tadesse Mekonen; Naemi Shoopala; Assegid Mengistu; Souleymane Sawadogo; Simon Agolory; Gram Mutandi; Valerie Garises; Rituparna Pati; Laura Tison; et al. (2020)
Abstract Background The Namibian Ministry of Health and Social Services (MoHSS) piloted the first HIV Project ECHO (Extension for Community Health Outcomes) in Africa at 10 clinical sites between 2015 and 2016. Goals of Project ECHO implementation included strengthening clinical capacity, improving professional satisfaction, and reducing isolation while addressing HIV service challenges during decentralization of antiretroviral therapy. Methods MoHSS conducted a mixed-methods evaluation to assess the pilot. Methods included pre/post program assessments of healthcare worker knowledge, self-efficacy, and professional satisfaction; assessment of continuing professional development (CPD) credit acquisition; and focus group discussions and in-depth interviews. Analysis compared the differences between pre/post scores descriptively. Qualitative transcripts were analyzed to extract themes and representative quotes. Results Knowledge of clinical HIV improved 17.8% overall (95% confidence interval 12.2–23.5%) and 22.3% (95% confidence interval 13.2–31.5%) for nurses. Professional satisfaction increased 30 percentage points. Most participants experienced reduced professional isolation (66%) and improved CPD credit access (57%). Qualitative findings reinforced quantitative results. Following the pilot, the Namibia MoHSS Project ECHO expanded to over 40 clinical sites by May 2019 serving more than 140 000 people living with HIV. Conclusions Similar to other Project ECHO evaluation results in the United States of America, Namibia’s Project ECHO led to the development of ongoing virtual communities of practice. The evaluation demonstrated the ability of the Namibia HIV Project ECHO to improve healthcare worker knowledge and satisfaction and decrease professional isolation.